2020
DOI: 10.1016/j.yhbeh.2019.104661
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin increases after affiliative interactions in male Barbary macaques

Abstract: Mammals living in stable social groups often mitigate the costs of group living through the formation of social bonds and cooperative relationships. The neuropeptide hormone oxytocin (OT) has been proposed to promote both bonding and cooperation although only a limited number of studies have investigated this under natural conditions. Our aim was to assess the role of OT in bonding and cooperation in male Barbary macaques (Macaca sylvanus). First we tested for an effect of affiliation -grooming and triadic mal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 93 publications
1
9
1
Order By: Relevance
“…CC-BY-ND 4.0 International license a certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made available under The copyright holder for this preprint (which was not this version posted March 18, 2020. ; https://doi.org/10.1101/765123 doi: bioRxiv preprint previous study on the same group of Barbary macaques we did not find an increase in oxytocin levels following triadic interactions in general but found that oxytocin levels were only higher after triadic interactions with non-bond partners (Rincon et al, 2020). If the combination of low testosterone and high oxytocin is responsible for bonding, then triadic interactions may function to form bonds selectively between non-bonded partners while physiologically not affecting existing bonds between strongly bonded partners.…”
Section: Discussioncontrasting
confidence: 71%
“…CC-BY-ND 4.0 International license a certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made available under The copyright holder for this preprint (which was not this version posted March 18, 2020. ; https://doi.org/10.1101/765123 doi: bioRxiv preprint previous study on the same group of Barbary macaques we did not find an increase in oxytocin levels following triadic interactions in general but found that oxytocin levels were only higher after triadic interactions with non-bond partners (Rincon et al, 2020). If the combination of low testosterone and high oxytocin is responsible for bonding, then triadic interactions may function to form bonds selectively between non-bonded partners while physiologically not affecting existing bonds between strongly bonded partners.…”
Section: Discussioncontrasting
confidence: 71%
“…Regarding social behavior, OXT secretion after positive social interaction is widely observed in primates [12][13][14][15], but the impact of relationship strength on OXT release is not yet well known. In one study on chimpanzees, urinary OXT concentration increased after grooming with a bonded partner, but not after the same interaction with a nonbonded partner [13]; on the contrary, two studies suggest that OXT secretion is independent of affiliative relationship strength [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary oxytocin concentrations of mantled howler monkeys were higher when individuals participated in affiliative interactions, a pattern also observed in capuchin monkeys, chimpanzees, common marmosets, Barbary macaques, and humans (Seltzer & Ziegler, 2007;Morhenn et al, 2008;Witting et al, 2014;Benítez et al, 2018;Rincon et al, 2020). However, whereas the relationship between oxytocin concentrations following affiliation and the quality of social relationships is positive in chimpanzees (Crockford et al, 2013), it was negative in mantled howler monkeys.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, oxytocin may be part of a positive feedback mechanism underlying socialization. This mechanism is both associated with positive interactions with peers (i.e., affiliation) and agonistic behavior (De Dreu, 2012;Anacker & Beery, 2013;Fujii et al, 2016;Samuni et al, 2016;Benítez et al, 2018;Cavanaugh et al, 2018;Rincon et al, 2020). In the latter, oxytocin facilitates the categorization of individuals as belonging to the same or another group, promoting cooperation and trust toward ingroup peers, but fear and distrust towards outgroup individuals (De Dreu, 2012;Fujii et al, 2016).…”
Section: Introductionmentioning
confidence: 99%